The prevalence of helicobacter pylori in referral population of Turkey - Usarov, Komiljon; Ahmedov, Anvarjon A.; Abasiyanik, Mustafa Fatih; Ku Muhammad Naim, Ku Khalif; Akhmedov, Abdulkasim (IOP Publishing Ltd, 2021)
Helicobacter pylori infection is commonly associated with gastroduodenal diseases in humans, such as chronic gastritis and peptic ulcers, gastric mucosa-associated lymphoid tissue lymphoma, and even gastric cancer, which leads to high cost to society for treatment and even to death many people, when people do not know early of the infection prevalence. In this work we proposed a forecasting model to predict the infection prevalence. Based on our results society can make simple early prevention acts against the infection. The early prevention acts decrease the cost of treatment and save many people's lives in the world.